Cathode and anode plate size matching method
By optimizing the size and materials of the cathode and anode plates and combining with the intelligent control system, the problem of mismatch in the size of the cathode and anode plates in zinc wet smelting is solved, and the electrolytic efficiency is improved, equipment life is extended and production costs is reduced.
Patent Information
- Application Number
- CN202411565345.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the traditional zinc wet smelting process, the mismatch of the size of the cathode and anode plates leads to low electrolytic efficiency, uneven zinc deposition, large equipment loss and unstable product quality, and the adjustment method lacks scientific basis.
The effective area of the designed cathode plate is larger than that of the anode plate, the length of the cathode plate is longer than that of the anode plate and the width is wider than that of the anode plate. Combined with high entropy alloy materials and adaptive nanocomposite coating, the current density is monitored and adjusted in real time through the intelligent control system to ensure the current The density is evenly distributed.
It improves electrolytic efficiency, extends the service life of the equipment, reduces production costs, ensures zinc deposition quality and stability of the electrolytic process, and reduces energy consumption and maintenance frequency.
Smart Images

Figure CN119243265A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of household kitchens, and in particular to a method for matching the sizes of anode and cathode plates. Background Art
[0002] Zinc hydrometallurgy is an important process in modern zinc metallurgy and is widely used in the extraction and purification of zinc. The process mainly relies on the electrochemical reaction between the cathode plate and the anode plate in the electrolytic cell to deposit zinc from the zinc-containing solution onto the cathode plate. However, in the traditional zinc hydrometallurgy process, there are often major problems in the design and matching of the anode and cathode plate sizes, which leads to many adverse phenomena in the electrolysis process, seriously affecting production efficiency and product quality.
[0003] Specifically, in the traditional process, due to the mismatch of the sizes of the cathode and anode plates, the current density at the edge of the cathode plate is often too high, thus forming dendritic zinc crystals. These dendritic crystals not only easily cause short circuits between the cathode and anode plates, affecting the electrolysis efficiency, but also make the zinc deposition uneven, increasing the difficulty of zinc stripping. In addition, when the cathode plate is too large, the current density is unevenly distributed, which will cause serious corrosion on the cathode plate surface and increase the cathode plate damage rate, thereby shortening the service life of the equipment and increasing maintenance and replacement costs.
[0004] In order to solve these problems, the industry has adjusted the size of the anode and cathode plates through empirical methods, but the results are often unsatisfactory and lack scientific basis, making it difficult to achieve precise control and efficient production. Therefore, there is an urgent need for a method that can scientifically design the size of the anode and cathode plates and combine it with intelligent control technology to optimize the current density distribution during the electrolysis process, prevent the formation of dendrites, improve the deposition quality of zinc, extend the service life of the equipment, and reduce production costs. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a method for matching the sizes of anode and cathode plates, which solves the problems of low electrolysis efficiency, uneven zinc deposition, large equipment loss and unstable product quality caused by mismatched sizes of anode and cathode plates in the prior art.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a method for matching the sizes of anode and cathode plates, comprising the following steps:
[0007] Determine the number of cathode plates and anode plates according to the internal dimensions of the electrolytic cell;
[0008] The effective area of the cathode plate is designed to be larger than the effective area of the anode plate, wherein the length of the cathode plate is longer than the length of the anode plate, and the width of the cathode plate is wider than the width of the anode plate;
[0009] The cathode plate and the anode plate are fixedly installed in the electrolytic cell respectively, so that the positions of the cathode plate and the anode plate in the electrolytic cell are relatively fixed, and the relative distance between the cathode plate and the anode plate is ensured to be unchanged;
[0010] During the electrolysis process, the current density on the cathode plate is controlled within a preset range, and the current density on the anode plate is adjusted according to the difference in area between the anode plate and the cathode plate to achieve a reasonable distribution of the current density.
[0011] Preferably, the length of the cathode plate is 10-50 mm longer than that of the anode plate, preferably 40 mm.
[0012] Preferably, the width of the cathode plate is 5-30 mm wider than that of the anode plate, preferably 21 mm.
[0013] Preferably, the internal positive and negative electrode plates of the electrolytic cell are arranged alternately and kept in parallel.
[0014] Preferably, the control range of the current density is 500-530A / m 2 The current density in each area of the electrolytic cell can be accurately adjusted by the actual size and number of the anode and cathode plates in the electrolytic cell.
[0015] Preferably, the cathode plate is made of a high entropy alloy material, which has high strength and corrosion resistance and can maintain structural stability and conductivity during long-term electrolysis.
[0016] Preferably, the surface of the anode plate is coated with an adaptive nanocomposite coating, which can adjust its surface microstructure according to the change of current density during the electrolysis process to reduce the corrosion of the anode plate and the formation of deposits.
[0017] Preferably, an intelligent control system is provided in the electrolytic cell, and the intelligent control system includes sensors for real-time monitoring of current density, temperature and electrolyte concentration, and can automatically adjust the current density of the anode and cathode plates and the electrolyte flow based on the monitoring data.
[0018] Preferably, the surface of the cathode plate is coated with an indium tin oxide coating, which has excellent conductivity and corrosion resistance and can reduce uneven deposition of zinc on the surface of the cathode plate.
[0019] Preferably, the cathode plate is fixed by a mechanical clamping device, which can ensure a fixed spacing between the cathode plate and the anode plate, while allowing fine adjustment of the position of the cathode plate during the electrolysis process.
[0020] The present invention provides a method for matching the sizes of anode and cathode plates. It has the following beneficial effects:
[0021] 1. The present invention significantly improves the overall efficiency of the electrolysis process by rationally designing the sizes of the cathode and anode plates; the effective area of the cathode plate is larger than that of the anode plate. Through this size optimization, the current density distribution in the electrolytic cell is more uniform, reducing the formation of dendritic zinc crystals caused by excessive current density at the edge of the cathode plate, thereby improving the zinc deposition efficiency.
[0022] 2. The present invention adopts a cathode plate made of high entropy alloy material and indium tin oxide coating, which not only improves the corrosion resistance and conductivity of the cathode plate, but also ensures that the deposition quality of zinc is more uniform and pure; through real-time adjustment of the intelligent control system, parameter abnormalities that may cause product quality fluctuations during the electrolysis process are avoided, so that the produced zinc ingots have a low lead content and meet higher industrial quality standards.
[0023] 3. The cathode plate of the present invention adopts high entropy alloy material, and the surface of the anode plate is coated with an adaptive nano-composite coating. These technical measures significantly improve the corrosion resistance and mechanical strength of the cathode and cathode plates in the electrolyte; through the application of these materials and coatings, the cathode and cathode plates maintain a stable structure and function during long-term electrolysis, greatly extending the service life of the equipment and reducing the frequency of equipment replacement and maintenance due to corrosion and wear.
[0024] 4. The present invention uses an intelligent control system to enable real-time monitoring and automatic adjustment of key parameters in the electrolysis process. This precise control method avoids abnormal conditions caused by parameter fluctuations in the electrolysis process, ensures the continuity and stability of the entire production process, and thus improves the operating efficiency and reliability of the production line.
[0025] 5. The present invention achieves more efficient current density distribution and electrolyte utilization by optimizing the size of the anode and cathode plates in the electrolytic cell and applying an intelligent control system. As the energy utilization rate in the electrolysis process is improved, unnecessary power consumption is reduced, thereby reducing overall energy consumption. At the same time, due to the extension of equipment life and the reduction of maintenance frequency, production costs are also significantly reduced, further improving the economic benefits of the entire smelting process. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Please see attached Figure 1 The present invention relates to a method for matching the size of anode and cathode plates, which aims to solve the problems of zinc dendrite precipitation, short circuit, reduced electrical efficiency, and corrosion damage of cathode plates caused by mismatched sizes of anode and cathode plates during zinc hydrometallurgy. Through the optimized design and matching installation of the sizes of anode and cathode plates, combined with the reasonable distribution and intelligent regulation of current density during electrolysis, the present invention can significantly improve the production efficiency and product quality of zinc, extend the service life of the equipment, and reduce overall energy consumption.
[0029] 1. Size design of anode and cathode plates
[0030] In the zinc hydrometallurgy process, the reasonable design of the size of the cathode and cathode plates is crucial to the stability and efficiency of the entire electrolysis process. According to the present invention, when designing the cathode and cathode plates, the number of cathode and cathode plates in the electrolytic cell is first determined according to the internal size of the electrolytic cell (such as 3540 mm × 1710 mm × 870 mm), and the specific size of the cathode and cathode plates is optimized.
[0031] Cathode plate size design:
[0032] In this embodiment, the length of the cathode plate is designed to be 40 mm longer than the length of the anode plate. In specific implementation, the initial length of the cathode plate is set to 1065 mm, and the length of the anode plate is set to 1025 mm. This length difference is achieved through precise cutting and processing technology to ensure that the cathode plate covers a larger electrolytic cell area than the anode plate. In order to ensure that this length difference can effectively reduce the risk of zinc forming dendrites at the edge of the cathode plate, the edge of the cathode plate is smoothed to reduce the current concentration phenomenon.
[0033] In this embodiment, the width of the cathode plate is designed to be 21 mm wider than the width of the anode plate. In specific implementation, the width of the cathode plate is set to 680 mm, and the width of the anode plate is set to 659 mm. By increasing the width, it can be further ensured that the deposition of zinc is more uniform and the edge effect is reduced. The edge width of the cathode plate has been experimentally verified to ensure that the zinc deposition is uniform and the electrolysis process is stable under this width difference.
[0034] Anode plate size design:
[0035] In this embodiment, the area of the anode plate is relatively small relative to the cathode plate to ensure a reasonable distribution of current density. The specific size of the anode plate is 1065 mm × 638 mm. After processing, the adaptive nanocomposite coating is coated on the premise of ensuring the surface conductivity and mechanical strength of the anode plate. The coating can be applied by a spraying process, and the coating thickness is controlled between 5 and 10 microns to ensure the corrosion resistance of the anode plate and the stability in the electrolyte.
[0036] 2. Installation of cathode and anode plates and current density adjustment
[0037] According to the present invention, the positive and negative poles are arranged alternately and fixed in parallel in the electrolytic cell according to the designed size and quantity, ensuring the relative position between the positive and negative poles is stable to maintain the uniform distribution of current during the electrolysis process.
[0038] Electrolyzer installation
[0039] In this embodiment, the number of cathode plates and anode plates installed in the electrolytic cell is 52. The cathode and anode plates are fixed by a mechanical clamping device, which is made of high-strength stainless steel material and has good corrosion resistance. The clamping device includes two side clamps and a top fixing clamp. During installation, the cathode plate and the anode plate are first placed in the fixing groove of the clamping device in turn, and then pressure is applied simultaneously by the side clamps and the top fixing clamp to ensure that the cathode and anode plates are fixed in the electrolytic cell. During installation, the spacing between the cathode plate and the anode plate is set to 50 mm to ensure uniform current distribution during the electrolysis process. This installation method can adapt to the changes in thermal expansion and contraction of the cathode and anode plates, and can be fine-tuned when necessary to maintain the stability of the entire system.
[0040] Current density regulation:
[0041] In this embodiment, during the electrolysis process, the current density on the cathode plate is controlled between 500 and 530 amperes per square meter. The current density on each cathode plate is monitored and adjusted by using an intelligent control system. The intelligent control system uses a multi-channel current controller to perform individual current regulation on each cathode plate. The current controller is connected to a sensor array, and the sensor detects the current density in real time and feeds back to the central processing unit. The central processing unit fine-tunes the current density based on a preset algorithm to ensure uniform distribution of current density throughout the electrolytic cell. In order to avoid damage to the cathode plate caused by excessive current density, the system adopts an adaptive regulation strategy when setting the working range of 500 to 530 amperes per square meter. In the actual electrolysis process, the current density is dynamically adjusted according to the surface temperature of the anode and cathode plates and the electrolyte concentration.
[0042] 3. Material selection and coating technology
[0043] In order to further improve the durability and electrolysis efficiency of the anode and cathode plates, the present invention optimizes the material selection of the anode and cathode plates and improves the surface coating.
[0044] Cathode plate material:
[0045] In this embodiment, the cathode plate is made of high entropy alloy material. The composition of this material includes various metal elements such as titanium, chromium, nickel, aluminum and iron, and is prepared by a vacuum melting process. The specific process steps include: first, after weighing each component in proportion, place it in a vacuum arc furnace for melting, the melting temperature is controlled at 1600 degrees Celsius, and the melting time is 30 minutes. Subsequently, the smelted high entropy alloy is cooled and cast to make a cathode plate blank. Finally, a high-strength, corrosion-resistant cathode plate is prepared by mechanical processing and surface treatment. This material can maintain good conductivity and mechanical strength under long-term electrolysis conditions to prevent the cathode plate from corroding or deforming in the electrolyte.
[0046] Anode plate coating:
[0047] In this embodiment, the surface of the anode plate is coated with an adaptive nano-composite coating. The coating materials include indium tin oxide, titanium dioxide and graphene, etc., which are prepared by a sol-gel method. The specific preparation steps of the coating are: first, a sol is prepared, and indium tin oxide, titanium dioxide and graphene nanopowders are added to a solvent in proportion, and a uniform coating sol is obtained through ultrasonic dispersion and mechanical stirring. Subsequently, the sol is evenly coated on the surface of the anode plate by a spraying process, and sintered at 400 degrees Celsius for 1 hour to form a dense nano-composite coating. The coating thickness is controlled at 5 to 10 microns, has good electrical conductivity and corrosion resistance, can automatically adjust the surface microstructure as the current density changes during the electrolysis process, and reduce the corrosion of the anode plate and the formation of deposits.
[0048] 4. Intelligent control system
[0049] In order to achieve efficient and stable operation of the electrolysis process, the present invention integrates an intelligent control system to monitor and automatically adjust multiple key parameters in the electrolytic cell in real time.
[0050] Real-time monitoring:
[0051] In this embodiment, the intelligent control system uses a multi-sensor array for real-time monitoring. The sensors include temperature sensors, current sensors, and electrolyte concentration sensors, which are installed at different positions on the cathode plate, anode plate, and electrolytic cell. The sensor data is transmitted to the central processing unit in real time through the wireless communication module. The central processing unit uses a high-performance processor to run a dedicated algorithm to analyze the sensor data in real time, and transmit the analysis results to the control system execution unit. Through this real-time monitoring method, the system can detect and adjust abnormal parameters in time during the electrolysis process to ensure the stable operation of the electrolysis process.
[0052] Dynamic Adjustment:
[0053] In this embodiment, based on the sensor feedback data, the intelligent control system can automatically adjust the current density on the anode and cathode plates and the flow rate and concentration of the electrolyte. The central processing unit uses the PID control algorithm to adjust according to the current density data fed back by the current sensor to ensure that the current density of the anode and cathode plates fluctuates within a preset range. The flow rate and concentration of the electrolyte are achieved by adjusting the electrolyte circulation pump and the liquid adding device. The system adjusts the liquid adding rate and flow rate in real time according to the data of the electrolyte concentration sensor to ensure the uniformity and stability of the electrolyte. The entire control system has a high degree of automation capability and can adapt to the electrolysis process requirements under different production conditions to ensure the efficiency and stability of zinc hydrometallurgy.
[0054] Example 1
[0055] Specific steps:
[0056] Electrolyzer size: internal dimensions are 3540 mm × 1710 mm × 870 mm.
[0057] Cathode plate dimensions: length 1105 mm, width 680 mm.
[0058] Anode plate dimensions: length 1065 mm, width 659 mm.
[0059] Current density: The cathode plate is controlled at 500 amperes per square meter.
[0060] Material selection: The cathode plate is made of high entropy alloy material, and the surface of the anode plate is coated with an adaptive nano-composite coating.
[0061] Intelligent control system: real-time monitoring of current density, temperature and electrolyte concentration, and automatic adjustment of the current density of the anode and cathode plates.
[0062] Process parameters:
[0063] Current density: 500 amperes per square meter.
[0064] Temperature: 35 degrees Celsius.
[0065] Electrolysis time: 72 hours.
[0066] Zinc deposition: 35 kg.
[0067] Example 2
[0068] Specific steps:
[0069] Electrolyzer size: internal dimensions are 3540 mm × 1710 mm × 870 mm.
[0070] Cathode plate dimensions: length 1125 mm, width 700 mm.
[0071] Anode plate dimensions: length 1085 mm, width 679 mm.
[0072] Current density: The cathode plate is controlled at 520 amperes per square meter.
[0073] Material selection: The cathode plate is made of titanium-based alloy and the anode plate is coated with indium tin oxide.
[0074] Intelligent control system: real-time monitoring and adjustment of electrolyte flow rate and concentration.
[0075] Process parameters:
[0076] Current density: 520 amperes per square meter.
[0077] Temperature: 37 degrees Celsius.
[0078] Electrolysis time: 70 hours.
[0079] Zinc deposition: 37 kg.
[0080] Example 3
[0081] Specific steps:
[0082] Electrolyzer size: internal dimensions are 3540 mm × 1710 mm × 870 mm.
[0083] Cathode plate dimensions: length 1130 mm, width 690 mm.
[0084] Anode plate dimensions: length 1090 mm, width 670 mm.
[0085] Current density: The cathode plate is controlled at 530 amperes per square meter.
[0086] Material selection: The cathode plate is made of stainless steel composite material, and the surface of the anode plate is coated with an adaptive nano-composite coating.
[0087] Intelligent control system: The control system combines temperature, concentration regulation and current monitoring.
[0088] Process parameters:
[0089] Current density: 530 amperes per square meter.
[0090] Temperature: 36 degrees Celsius.
[0091] Electrolysis time: 68 hours.
[0092] Zinc deposition: 36 kg.
[0093] Example 4
[0094] Specific steps:
[0095] Electrolyzer dimensions: Internal dimensions are 3540 mm × 1710 mm × 870 mm. Cathode plate dimensions: Length is 1150 mm, width is 710 mm.
[0096] Anode plate dimensions: length 1110 mm, width 690 mm.
[0097] Current density: The cathode plate is controlled at 525 amperes per square meter.
[0098] Material selection: The cathode plate is made of titanium alloy and the anode plate is coated with an adaptive nano-composite coating.
[0099] Intelligent control system: optimize current density regulation, combined with electrolyte concentration monitoring. Process parameters:
[0100] Current density: 525 amperes per square meter.
[0101] Temperature: 38 degrees Celsius.
[0102] Electrolysis time: 66 hours.
[0103] Zinc deposition: 38 kg.
[0104] Example 5
[0105] Specific steps:
[0106] Electrolyzer dimensions: Internal dimensions are 3540 mm × 1710 mm × 870 mm. Cathode plate dimensions: Length is 1145 mm, width is 705 mm.
[0107] Anode plate dimensions: length 1105 mm, width 685 mm.
[0108] Current density: The cathode plate is controlled at 515 amperes per square meter.
[0109] Material selection: The cathode plate is made of high entropy alloy, and the surface of the anode plate is coated with indium tin oxide.
[0110] Intelligent control system: real-time monitoring and dynamic adjustment of current density and electrolyte temperature. Process parameters:
[0111] Current density: 515 amperes per square meter.
[0112] Temperature: 37 degrees Celsius.
[0113] Electrolysis time: 69 hours.
[0114] Zinc deposition: 37.5 kg.
[0115] Comparative Example
[0116] Comparative Example 1
[0117] Specific steps:
[0118] Electrolyzer dimensions: Internal dimensions are 3540 mm × 1710 mm × 870 mm. Cathode plate dimensions: Length is 1050 mm, width is 650 mm.
[0119] Anode plate dimensions: length 1050 mm, width 650 mm.
[0120] Current density: The cathode plate is controlled at 500 amperes per square meter, without dynamic adjustment. Material selection: The cathode plate is made of stainless steel, and the anode plate has no special coating on the surface.
[0121] Process parameters:
[0122] Current density: 500 amperes per square meter.
[0123] Temperature: 35 degrees Celsius.
[0124] Electrolysis time: 72 hours.
[0125] Zinc deposition: 33 kg.
[0126] Comparative Example 2
[0127] Specific steps:
[0128] Electrolyzer dimensions: Internal dimensions are 3540 mm × 1710 mm × 870 mm. Cathode plate dimensions: Length is 1060 mm, width is 660 mm.
[0129] Anode plate dimensions: length 1060 mm, width 660 mm.
[0130] Current density: The cathode plate is controlled at 510 amperes per square meter, without dynamic adjustment. Material selection: The cathode plate is made of ordinary steel, and the surface of the anode plate is coated with indium tin oxide.
[0131] Process parameters:
[0132] Current density: 510 amperes per square meter.
[0133] Temperature: 37 degrees Celsius.
[0134] Electrolysis time: 72 hours.
[0135] Zinc deposition: 34 kg.
[0136] Data Table
[0137] Table 1:
[0138]
[0139]
[0140] Experimental example
[0141] Experimental objective: To verify the advantages of the anode and cathode plate size matching method of the present invention over the traditional method.
[0142] Experimental methods:
[0143] The same electrolytic cell dimensions (3540 mm × 1710 mm × 870 mm) and electrolyte formulation were used.
[0144] The differences in the size, material, coating, intelligent control system, etc. of the anode and cathode plates between the experimental group (Example 1) and the control group (Comparative Example 1) were compared.
[0145] The zinc deposition amount, current density, temperature and electrolysis time of each group were recorded.
[0146] Experimental data table:
[0147]
[0148]
[0149]
[0150] According to the table, the zinc deposition amount and zinc ingot purity in Examples 1-5 are higher than those in Comparative Examples 1-2. Specifically:
[0151] Zinc deposition amount: The zinc deposition amount of the embodiments is generally higher than that of the comparative examples, which indicates that the optimized anode and cathode plate size design and material selection can significantly improve the zinc deposition efficiency.
[0152] Purity of zinc ingot: The purity of the zinc ingot of the embodiment is also better than that of the comparative example, indicating that through reasonable design and intelligent control, the deposition quality of zinc is higher and the impurity content is lower.
[0153] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for matching the size of anode and cathode plates, characterized in that: The following steps are involved: Determine the number of cathode plates and anode plates according to the internal dimensions of the electrolytic cell; The effective area of the cathode plate is designed to be larger than the effective area of the anode plate, wherein the length of the cathode plate is longer than the length of the anode plate, and the width of the cathode plate is wider than the width of the anode plate; The cathode plate and the anode plate are fixedly installed in the electrolytic cell respectively, so that the positions of the cathode plate and the anode plate in the electrolytic cell are relatively fixed, and the relative distance between the cathode plate and the anode plate is ensured to be unchanged; During the electrolysis process, the current density on the cathode plate is controlled within a preset range, and the current density on the anode plate is adjusted according to the difference in area between the anode plate and the cathode plate to achieve a reasonable distribution of the current density.
2. A method for matching the sizes of anode and cathode plates according to claim 1, characterized in that: The length of the cathode plate is 10-50 mm longer than that of the anode plate, preferably 40 mm.
3. A method for matching the sizes of anode and cathode plates according to claim 1, characterized in that: The width of the cathode plate is 5-30 mm wider than that of the anode plate, preferably 21 mm.
4. A method for matching the sizes of anode and cathode plates according to claim 1, characterized in that: The positive and negative electrodes in the electrolytic cell are arranged alternately and kept in parallel.
5. A method for matching the sizes of anode and cathode plates according to claim 1, characterized in that: The control range of the current density is 500-530A / m 2 The current density in each area of the electrolytic cell can be accurately adjusted by the actual size and number of the anode and cathode plates in the electrolytic cell.
6. A method for matching the sizes of anode and cathode plates according to claim 1, characterized in that: The cathode plate is made of a high entropy alloy material, which has high strength and corrosion resistance and can maintain structural stability and conductivity during long-term electrolysis.
7. A method for matching the sizes of anode and cathode plates according to claim 6, characterized in that: The surface of the anode plate is coated with an adaptive nanocomposite coating, which can adjust its surface microstructure according to the change of current density during electrolysis to reduce the corrosion of the anode plate and the formation of deposits.
8. A method for matching the sizes of anode and cathode plates according to claim 1, characterized in that: An intelligent control system is provided in the electrolytic cell, which includes sensors for real-time monitoring of current density, temperature and electrolyte concentration, and can automatically adjust the current density of the anode and cathode plates and the electrolyte flow based on the monitoring data.
9. A method for matching the sizes of anode and cathode plates according to claim 8, characterized in that: The surface of the cathode plate is coated with an indium tin oxide coating, which has excellent conductivity and corrosion resistance and can reduce uneven deposition of zinc on the surface of the cathode plate.
10. A method for matching the sizes of anode and cathode plates according to claim 1, characterized in that: The cathode plate is fixed by a mechanical clamping device, which can ensure a fixed distance between the cathode plate and the anode plate, while allowing fine adjustment of the position of the cathode plate during the electrolysis process.
